Origin and destination of urban solid waste and knowledge of residents of the Municipality of Cambuci - RJ (Research, Society and Development, 2023)
This study has the general objective of identifying the main sources and destination of urban solid waste in the municipality of Cambuci-RJ, as well as analyzing the speeches of residents regarding environmental issues. This article is an excerpt from the first author's course conclusion work. The research is justified by the need to broaden the understanding of waste production. This is a qualitative research, with data obtained from the application of questionnaires with open and closed questions. Twenty residents and twenty-six establishments (including health centers, hospitals and pharmacies) participated in the survey. Respondents did not demonstrate high ecological awareness, as most of them do not separate garbage. Many are not concerned with the garbage they produce, and there is no action by the government to mitigate the problems generated, not even to make the population aware of environmental issues. As for the establishments visited, there is an effort to do what is right in relation to the environment, however, this is not always feasible. We conclude that there is a lack of communication between the Municipal Secretary of the Environment and the population, which means that environmental issues are not a priority among residents.